M-HIFU Inhibits Tumor Growth, Suppresses STAT3 Activity and Enhances Tumor Specific Immunity in a Transplant Tumor Model of Prostate Cancer - Huang, Xiaoyi (Public Library of Science, 2012)
OBJECTIVE: In this study, we explored the use of mechanical high intensity focused ultrasound (M-HIFU) as a neo-adjuvant therapy prior to surgical resection of the primary tumor. We also investigated the role of signal transducer and activator of transcription 3 (STAT3) in M-HIFU elicited anti-tumor immune response using a transplant tumor model of prostate cancer. METHODS: RM-9, a mouse prostate cancer cell line with constitutively activated STAT3, was inoculated subcutaneously in C57BL/6J mice. The tumor-bearing mice (with a maximum tumor diameter of 5∼6 mm) were treated by M-HIFU or sham exposure two days before surgical resection of the primary tumor. Following recovery, if no tumor recurrence was observed in 30 days, tumor rechallenge was performed. The growth of the rechallenged tumor, survival rate and anti-tumor immune response of the animal were evaluated. RESULTS: No tumor recurrence and distant metastasis were observed in both treatment groups employing M-HIFU + surgery and surgery alone. However, compared to surgery alone, M-HIFU combined with surgery were found to significantly inhibit the growth of rechallenged tumors, down-regulate intra-tumoral STAT3 activities, increase cytotoxic T cells in spleens and tumor draining lymph nodes (TDLNs), and improve the host survival. Furthermore, M-HIFU combined with surgery was found to significantly decrease the level of immunosuppression with concomitantly increased number and activities of dendritic cells, compared to surgery alone. CONCLUSION: Our results demonstrate that M-HIFU can inhibit STAT3 activities, and when combined synergistically with surgery, may provide a novel and promising strategy for the treatment of prostate cancers.